Pendidikan Inklusif Berbasis Kebudayaan: Menyelaraskan Kearifan Lokal Dengan Kurikulum Pendidikan - Tanjung, Ferdian (Universitas Tanjungpura, 2024)
This study aims to explore the integration of local wisdom into inclusive education curricula and to examine how culturally-based approaches can enhance the effectiveness of inclusive education. The research seeks to bridge the gap between traditional cultural values and modern educational practices, providing insights into the alignment of local wisdom with inclusive education principles. This research employs a mixed-methods approach, combining case study and survey techniques. The case study involves an in-depth analysis of selected schools that have successfully integrated local wisdom into their inclusive education programs. Data is collected through interviews with school leaders, teachers, and community members, as well as classroom observations. The survey targets educators, school administrators, and policymakers to collect quantitative data on their perspectives and experiences regarding the integration of local wisdom into inclusive education. Results: Preliminary findings indicate that integrating local wisdom into inclusive curricula can enhance cultural relevance and student engagement. Schools that effectively blend local traditions with inclusive practices demonstrate improved educational outcomes and greater community support. However, challenges such as resistance to change and resource limitations are also identified. Conclusion: The integration of local wisdom into inclusive education presents both opportunities and challenges. This study highlights the importance of aligning educational practices with cultural values to foster a more inclusive and contextually relevant learning environment. Recommendations for policy and practice include increased support for culturally responsive training and the development of resources that facilitate the integration of local wisdom into educational curricula.